Determination of salival PH in adult patients with compensated diabetes mellitus - Avellaneda Lopez, María Dayan (2021)
Objective. Determine salivary pH in compensated adult patients with diabetes mellitus (DM) treated at the Callao public health center. Material and methods. It was an analytical, observational, case-control study. Sample of 50 people with an age range of 20 to 60 years. A general induction on the study was carried out to obtain informed consent. A general induction on the study was carried out to obtain informed consent. They were instructed to contain the saliva that accumulates in the mouth for a few minutes and then, each minute, the saliva was poured into a glass funnel connected to a clean, disinfected cylinder, graduated in 10ml, this activity was carried out during a minute. Once the sample was collected, it was placed in a cool and safe place to allow it to rest for a few minutes and then be able to proceed to measure its pH with the digital pH meter and immediately place the results obtained in the individual data sheet. Results. On average, the salivary pH of people with diabetes mellitus (pH = 6.5) is lower than that of people who do not have the disease (pH = 8.3), which indicates that they have a more acidic salivary pH. Conclusion. On average, the salivary pH of diabetic people is lower than healthy people, which indicates that they have a more acidic salivary pH; likewise, diabetic patients have an OSI higher on average than healthy people.